2016
DOI: 10.1111/cns.12663
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Maternal Deprivation Enhances Presynaptic P2X7 Receptor Transmission in Insular Cortex in an Adult Rat Model of Visceral Hypersensitivity

Abstract: Data suggested that the enhanced activities of P2X7Rs in IC, likely through a presynaptic mechanism, contributed to visceral hypersensitivity of adult rats with NMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
(68 reference statements)
4
16
0
Order By: Relevance
“…This implies that the acute stress causes visceral responses more often and earlier than somatic responses. Consistent with previous studies that stress led to colonic hypersensitivity 41,42 and functional dyspepsia-like gastric hypersensitivity in rats, 7 which was most likely mediated by stress hormones such as CORT and epinephrine, we demonstrated for the first time that CORT injection induced gastric hypersensitivity in normal rats. However, the detailed mechanisms of systematic application CORT are not well understood.…”
Section: Discussionsupporting
confidence: 91%
“…This implies that the acute stress causes visceral responses more often and earlier than somatic responses. Consistent with previous studies that stress led to colonic hypersensitivity 41,42 and functional dyspepsia-like gastric hypersensitivity in rats, 7 which was most likely mediated by stress hormones such as CORT and epinephrine, we demonstrated for the first time that CORT injection induced gastric hypersensitivity in normal rats. However, the detailed mechanisms of systematic application CORT are not well understood.…”
Section: Discussionsupporting
confidence: 91%
“…Chronic visceral hyperalgesia was induced by NMD and assessed by colorectal distension (CRD) threshold as described previously. 12 , 16 Experiments were performed in NMD rats at age of 6 to 7 weeks. The age-matched healthy male rats were used as control (CON).…”
Section: Methodsmentioning
confidence: 99%
“…Our recent report that neonatal maternal deprivation (NMD) enhances synaptic transmission by sensitization of P2X7Rs in right IC suggests an alteration of synapse plasticity in IC. 12 Studies from clinic perspective also provided several lines of evidence to strongly support an involvement of IC in chronic visceral hypersensitivity of patients with irritable bowel syndrome (IBS). Using a task-dependent functional magnetic resonance imaging technique to investigate the brain activity, two groups showed that hypersensitive patients with IBS had greater activation of insula and reduced deactivation in pregenual anterior cingulate cortex during noxious rectal distensions, compared to controls and normosensitive patients with IBS.…”
Section: Introductionmentioning
confidence: 99%
“…For behavioral tests and molecular measurements, AAV-NC or AAV-P2X4R from Genechem Co. Ltd (Shanghai, China) was stereotaxically microinjected into the hippocampus of T2DM rats as described in our previous study [22]. Briefly, after the rat was anesthetized by intraperitoneal injection of 4% chloral hydrate, a microinjector was fixed unilaterally to the left side of the skull and aimed at the hippocampus (coordinates with respect to bregma: AP -4.8 mm, ML 3.2 mm, DV 3.5 mm, angle 0°) or at the right hippocampus.…”
Section: Microinjection Of Adeno-associated Virus (Aav)mentioning
confidence: 99%
“…ATP that supplies energy for cellular metabolism can be released into the extracellular space and play an important role via purinergic 2 receptors (P2Rs) in mediating neurotransmission as well as Ca 2? waves between astrocytic glial cells [21,22]. In addition, ATP released locally from damaged tissue induces microgliosis, and activated microglial cells migrate to the site of injury, proliferate, and phagocytose cells and cellular components [23].…”
Section: Introductionmentioning
confidence: 99%